2013
DOI: 10.1080/02643294.2013.853655
|View full text |Cite
|
Sign up to set email alerts
|

When does action comprehension need motor involvement? Evidence from upper limb aplasia

Abstract: Motor theories of action comprehension claim that comprehending the meaning of an action performed by a conspecific relies on the perceiver's own motor representation of the same action. According to this view, whether an action belongs to the motor repertoire of the perceiver should impact the ease by which this action is comprehended. We tested this prediction by assessing the ability of an individual (D.C.) born without upper limbs to comprehend actions involving hands (e.g., throwing) or other body parts (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 87 publications
2
12
0
Order By: Relevance
“…Our findings thus considerably extend previous results obtained with IDs or congenital paralysis (19,(32)(33)(34)(35). It has been shown that individuals with congenital paralysis of facial muscles recognize facial expressions despite their inability to perform facial movements (32).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Our findings thus considerably extend previous results obtained with IDs or congenital paralysis (19,(32)(33)(34)(35). It has been shown that individuals with congenital paralysis of facial muscles recognize facial expressions despite their inability to perform facial movements (32).…”
Section: Discussionsupporting
confidence: 72%
“…The observation reported here that IDs 1, 2, and 3 were better at recognizing non-upper limb actions than upper limb actions in experiment 2 (see also ref. 19) and that ID3 was impaired in predicting the outcome of the basketball free shot in experiment 5 also point to this possibility (although this difficulty also could be explained by the IDs having different visual experiences of these actions). Collectively, these results call for the development of fresh hypotheses about how knowledge acquired through motor experience helps shape visually and conceptually based computations of body actions.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Participant D.C. is a 53-year-old man whose performance in various experiments has already been reported (Vannuscorps, Pillon & Andres, 2012;Vannuscorps, Andres & Pillon, 2013, 2014. He has a master's degree in psychopedagogy.…”
Section: Methodsmentioning
confidence: 99%